Legal Consequences of Difference in The Results of Two Visum Et Repertum in Proving Criminal Case in Indonesia - Firmansyah, Muhammad; Simangunsong, Frans (Jurnal Hukum Magnum Opus, 2024)
In criminal cases, visual evidence is used to reveal the cause and effect of a criminal act. If there are two different visual outcomes in Brigadier Joshua's case, then the question arises as to which choice of visum will be recognized as valid evidence by the judge in considering his decision. The formulation of the problem in this study is how the legal consequences of the difference in the results of two visum et repertum in the evidence system in Indonesia. This study aims to examine the legal consequences of the difference in the results of the two visum et repertum in proving criminal cases in Indonesia. This study used normative legal research. The approach used in this study is to use a statutory approach and a conceptual approach. The results of this study showed that the case of the visual results in Brigadier Josua had 2 different results. Therefore, the principle of Indonesian criminal procedural law, finding material truth is very important in proof in the criminal justice process. What is meant by "incriminalibus probantiones bedent esse luce clariores" is that evidence in a criminal case must be brighter than clear. There will be legal confusion in determining which law enforcement officials will be used as a benchmark in assessing valid evidence according to the rules of the Criminal Procedure Code if there are differences in the results of visum et repertum in a criminal case. The procedures outlined in the Instruction of the Chief of Police Number: INS/E/ 20/IX/75 concerning procedures for making visum et repertum and its revocation must be followed in making visum et repertum. To find out the cause and effect of a criminal act that occurs, as well as to collect information and seek the objective truth of a criminal act related to the relationship between the act and the consequences it causes.